2016
DOI: 10.1016/j.tet.2016.03.038
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of functionalized benzoboroxoles as potential anti-tuberculosis agents

Abstract: Several derivatives of aminobenzoboroxole have been prepared starting from 2-boronobenzaldehyde. All of these derivatives have been evaluated for their anti-mycobacterial activity on Mycobacterium smegmatis and cytotoxicity on breast cancer cell line MCF7. Based on these studies, all the tested molecules have been found to be generally non-toxic and benzoboroxoles with unsubstituted (primary) amines have been found to exhibit good anti-mycobacterial activity. Some of the key compounds have been evaluated for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 53 publications
(12 reference statements)
0
10
0
Order By: Relevance
“…132,133 In addition, benzoboroxoles also show inhibitory activity against several enzymes such as carbonic anhydrases and they are potential anti-tuberculosis agents. 134,135 However, this class of compound has recently drawn particular interest from their potential application as carbohydrate receptors, as they can bind sugars under physiological conditions. 136 Compared to their boronic acid counterparts, benzoboroxoles are able to bind sugars in the pyranose form, at pH values that are more suitable for biological systems.…”
Section: Benzoboroxolesmentioning
confidence: 99%
“…132,133 In addition, benzoboroxoles also show inhibitory activity against several enzymes such as carbonic anhydrases and they are potential anti-tuberculosis agents. 134,135 However, this class of compound has recently drawn particular interest from their potential application as carbohydrate receptors, as they can bind sugars under physiological conditions. 136 Compared to their boronic acid counterparts, benzoboroxoles are able to bind sugars in the pyranose form, at pH values that are more suitable for biological systems.…”
Section: Benzoboroxolesmentioning
confidence: 99%
“…Zhang et al described a set of interesting, highly active chalcone-benzoxaborole hybrids [14], but further studies are needed to reveal to what extent the observed activity resulted from the introduction of the boron-containing moiety. Suman et al synthesized a series of 6-aminobenzoxaborole derivatives, of which some showed high antiproliferative activity in pancreatic cancer cells (MIA-PaCa-2) [17], whereas some other examples of 6-aminobenzoxaborole-derived compounds showed no activity in MCF7 at a concentration of 50 μM [40], similarly to a set of β-ketobenzoxaboroles synthesized by Sravan Kumar et al [18]. In both cases, the described compounds had a much more complex chemical structure than the derivatives reported herein.…”
Section: Discussionmentioning
confidence: 99%
“…The BCG-vaccine Danish Strain 1331 (BCG-vaccine) from Chile (Statens Serum Institute, Denmark) and the NIH BCG-brain and BCG-lung clinical isolates were confirmed as M. tuberculosis complex by Maldi-TOF-MS and antibiotic susceptibility was performed. Antibiotic susceptibility testing of clinical and vaccine strains was performed as described previously ( table 2 ) [ 15 ].…”
Section: Methodsmentioning
confidence: 99%